Pembuatan Dan Karakterisasi Bolus Berbahan Beeswax Dengan Variasi Komposisi Massa Petrolleum Jelly - Milania Ada Loveleace Murmana; Alimin Mahyudin; Rico Adrial; Fiqi Diyona (Jurnal Fisika Unand, 2026)
The manufacture and characterization of beeswax bolus with various petroleum jelly mass compositions using a thermal mixing method has been carried out. Boluses measuring 10×10 cm with a thickness of 1.0 cm were characterized based on physical properties (density and water absorption), mechanical (tensile strength, strain, and elastic modulus), Relative Electron Density (RED), and absorbed dose. The results showed that the mass composition significantly influenced the bolus characteristics. The sample with a composition of 90:30 had a density of 0.966 g/cm³ which was closest to soft tissue, while the water absorption was in the range of 7.22– 8.54% with the lowest value at the composition of 85:35. Increasing the petroleum jelly content decreased the tensile strength and elastic modulus (1138–2251 MPa), indicating that the material became more flexible. Measurement of the absorbed dose at electron energies of 6 and 9 MeV and RED analysis of CT images showed that the dosimetric response was influenced by the mass composition, with certain RED values equivalent to breast tissue. Overall, the 85:35 composition provides the closest characteristics to human soft tissue and has the potential to be used as a radiotherapy bolus.